The Dynamics of Backpacker Umrah within the Framework of Maqashid Asy-Syariah and Sociology of Law - Hikmah, Nurul; Musyafaah, Nur Lailatul; Syafaq, Hammis; Shavia, Andina Najma; Ali, Mohammed Ramadhan Abraheem Alshaykh (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The backpacker umrah phenomenon reflects the community’s aspiration to perform worship in a more flexible and economical manner, yet it simultaneously generates serious concerns from both positive law and sharī’ah perspectives, as it is conducted outside the framework of official state mechanisms. This study analyzes backpacker Umrah from the perspective of Maqashid al-Shariah and legal sociology and offers ideal regulations that protect pilgrims. This research is an empirical legal study that uses primary data from a Google Form questionnaire to analyze the reasons and objectives of pilgrims performing Umrah as backpackers, supported by legal materials in the form of statutory regulations. The research findings demonstrate that the phenomenon of backpacker umrah embodies broader social dynamics and represents community responses to economic constraints and technological developments, as pilgrims increasingly opt for a more flexible and affordable mode of worship. In the perspective of legal sociology and maqashid asy-syariah, this practice demonstrates a culturally legitimate social construction, but it creates tension with formal regulations, particularly in aspects of security, legal protection, and compliance with legislation. Although it provides benefits to some segments of society, backpacker umrah still carries potential harms that need to be addressed proportionally. Based on the findings of this study, it is recommended that regulations governing ḥajj and umrah be more effectively organized to prevent long queues for pilgrims, and that specific provisions addressing backpacker umrah be formulated to ensure legal protection, along with guarantees of safety and comfort for those undertaking the pilgrimage independently.